Policing Images. - Mawby, R. I. (Taylor and Francis, 2013)
In recent years the police have become one of the most watched and most visible organisations, and across the media there has been constant interest in the police. In such a situation the police themselves have been intensely concerned with promoting, projecting and protecting the police image. This book is concerned to document and to explain this image work, the activities in which the police engage that construct and project images of policing. Drawing upon first-hand research with the police themselves (including such examples as the way the South Yorkshire Police handled the Min.